Evaluation of Total Mixed Rations in Terms of Nutrient Utilisation, Methane Production and Gaseous Exchange in Cattle and Buffaloes - Sinha, S. K.; Chaturvedi, V. B.; ,, P. Singh; Verma, A. K.; ,, Swati Shivani (Indian Journal of Animal Nutrition, 2018)
The present experiment was conducted to find out the effect of different ratios of concentrate, wheat straw and green fodder in rations on methane (CH4) production, gaseous exchange and heat production in crossbred cattle and buffaloes. After every one month of experimental feeding, CH4, heat production andgaseous exchange (CO2 and O2) were determined using open circuit respiration calorimetry in six adult crossbred cattle (Bos taurus × Bos indicus) and buffaloes (Bubalus bubalis) with average BW of 257.011±7.34 and 319.56±10.86 kg, respectively (age: 12-18 mo.). Experimental feeding consisted of three ratios ofconcentrate, wheat straw and green maize fodder i.e. 60: 20: 20 (T1), 40:30:30 (T2) and 20:40:40 (T3) fed as TMR alternatively to each group. The DM and OM intake in all the treatments and species were similar. The digestibility of DM and OM was different (P